Determinants of Skill Levels of Farm Youth with regard to Agripreneurship: A Multinomial Regression Approach (Indian Journal of Extension Education, 2021)
This study investigated various determinants of the differential level of skill as perceived by farm youth engaged in agripreneurship. The existing agripreneurial skill levels were delineated by developing a composite index constituting of 5 skill dimensions. Purposive sampling was adopted to select the rural youth belonging to farming background and involved in agripreneurship for higher income in five districts of Odisha representing five different agro-climatic zones. A total of 250 farm youth was sampled from the selected 10 blocks. The findings of the study revealed that, annual income from primary occupation, agripreneurial training, social media exposure and agripreneurship experience have significantly affected the existing level of skill possessed by farm youth with regard to agripreneurship. The findings affirm the need for extension personnel to understand the existing skill level, capacities, abilities of farm youth along with the factors determining them in order to create awareness and build capacities required for agripreneurship.